Origins of the Federal Judiciary : Essays on the Judiciary Act of 1789. - Marcus, Maeva (Oxford University Press, 1992)
A study of the origins of the Judiciary Act of 1789, the legislation that established the federal court system of the USA. This volume of essays analyzes the Judiciary Act from political, economic and legal perspectives, bringing together insights from scholars in a number of fields.